The Joint Analysis of Survival Times and Response Rates in Clinical Trials on the Treatment of Cancer - Wahrendorf, J. (Methods of Information in Medicine, 1980)
A method is outlined which allows to analyse survival and response data from a clinical trial on the treatment of cancer when the question of interest is whether the somehow defined response to the treatment has an influence on patients’ survival times. This can be done by making use of Cox’s proportional hazards model for survival data together with time-dependent covariates. This allows an appropriate classification of non-respondors and responders by considering the time of diagnosis of response during follow-up. The resulting test can be viewed as a time-dependent logrank test. An example from a clinical trial on gastrointestinal cancer is considered.
Keywords: Censored Data; Logrank Test; Proportional Hazards Model; Response Rates; Survival Data; Time-dependent Covariates